Management of Reprographic Services In Libraries & Information Centres - Rangra, V.K. (DESIDOC Journal of Library & Information Technology, 2002)
Explains briefly broad areas of reprography. Describes xerographic process and growth of the reprographic industry with special reference to plain paper copier (PPC). Gives criteria for selection of PPC and tabulates data of four prominent full colour PPCs. Gives details of a new portable colour PPC. Discusses the problem of copyright in photo-copying and charging for the photocopy/xerox service.